2011
DOI: 10.1158/1055-9965.epi-10-1160
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) 6, 11, 16, and 18 Seroprevalence Is Associated with Sexual Practice and Age: Results from the Multinational HPV Infection in Men Study (HIM Study)

Abstract: Background Few human papillomavirus (HPV) serology studies have evaluated type-specific seroprevalence of vaccine HPV types in men. This study investigates seroprevalence of HPV 6, 11, 16, and 18, and associated risk factors in men residing in three countries (United States, Mexico, and Brazil). Methods Data from 1,477 men aged 18 to 70 enrolled in the HPV Infection in Men Study (HIM Study) were analyzed. Serum antibody testing was performed with virus-like particle-based ELISA. Potential risk factors were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
52
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 47 publications
16
52
1
1
Order By: Relevance
“…This age-related pattern has consistently been described in serology studies among men (16,39,40,46) and may reflect cumulative lifetime HPV exposure in combination with age-related changes in immunity. An increasing number of lifetime male sex partners is a well-known risk factor for HPV infection (6), and showed a strong and significant association with HPV seropositivity in HIV-negative but not in HIV-infected MSM.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This age-related pattern has consistently been described in serology studies among men (16,39,40,46) and may reflect cumulative lifetime HPV exposure in combination with age-related changes in immunity. An increasing number of lifetime male sex partners is a well-known risk factor for HPV infection (6), and showed a strong and significant association with HPV seropositivity in HIV-negative but not in HIV-infected MSM.…”
Section: Discussionsupporting
confidence: 65%
“…Prevalence of antibodies against HPV-16, which is the most carcinogenic and therefore most important HPV type, was high compared to other studies among (mostly heterosexual) males (16,17,34,41), but comparable to data reported for MSM specifically (40,42). However, comparisons between HPV serology studies are hampered by major differences in characteristics of the study population and in serology methods.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…However, the prevalence of genital HR-HPV in male sexual partners of HR-HPV infected women was lower than that expected, and the concordance of high risk viral types between couples was extremely low. Based on our current knowledge, high risk sexual behaviors were strong determinants of HR-HPV infection in men, and the male patients with HPV 6/11 infection from STD outpatient clinic mostly had high frequency of sexual intercourse with multiple sexual partners, even prostitutes over lifetime (Lu et al, 2011) . But there was no statistical significance in the incidence of genital HR-HPV infection between men with (6.85%) and without (8.16%) HPV 6/11 in our study.…”
Section: Discussionmentioning
confidence: 93%
“…HPV seropositivity has been associated with both virus-related (e.g., regarding persistence of infection, viral load, and viral type) and host-related factors (e.g., increasing age, HIV-induced immunosuppression, anatomic site of infection, and sexual risk behavior; refs. 7,9,11,12). The very high antibody concentrations observed after HPV vaccination confer protection against incident HPV infection (13,14), but to what extent naturally induced antibodies also confer protection is still a matter of debate (9).…”
Section: Introductionmentioning
confidence: 99%